Klicka på ikonen: Populärmusikaliska historieskrivningar på youtube - Hyltén-Cavallius, Sverker (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2009)
In 2007, the BMI awarded Peter Gabriel as "Icon of the year". But how are such icons formed on a day-to-day basis? Youtube, a typical example of web 2.0 products, every day has 90 million visitors out of whom 1 percent actively interact on its platform, sharing and commenting videos. This article analyses different ways of narrating history in members’ comments on a video clip reproducing the song "The battle of Epping forest" from a Genesis concert from 1974. Three major kinds of historiography are discerned. First, the video reproduction in itself and in its relation to other videos from the same channel (tommygun1028) as forms of self-presentations and genre histories. Second, the members’ comments on the video as a form of artist-, band- and genre histories, where certain aspects are mutually agreed upon, while others are debated. And thirdly, these comments as fragments of life histories, claiming both "I was there" and "I wasn’t there" with equal authority, and pointing to links between music, text and personal biographies. To conclude, youtube establishes a platform where popular icons are formed in a polyphony of histories making use of the mythical room created between fans, industry, musicians and youtube members.